Assembling the Healthopolis: Competitive city‐regionalism and policy boosterism pushing Greater Manchester further, faster. Issue 2 (6th December 2020) - Lorne, Colin; Coleman, Anna; McDonald, Ruth; Walshe, Kieran
Abstract : Health and care policy is increasingly promoted within visions of the competitive city‐region. This paper examines the importance of policy boosterism within the political construction of city‐regions in the context of English devolution. Based on a two‐year case study of health and social care devolution in Greater Manchester, England, we trace the relational and territorial geographies of policy across and through new "devolved" city‐regional arrangements. Contributing to geographical debates on policy assemblages and city‐regionalism, we advance a conceptual framework linking crisis and opportunity, emulation and exceptionalism, and evidence and experimentation. The paper makes two key contributions. First, we argue health and care policy is increasingly drawn towards the logic of global competitiveness without being wholly defined by neoliberal political agendas. Fostering transnational policy networks helped embed global "best practice" policies while simultaneously hailing Greater Manchester as a place beyond compare. Second, we caution against positioning the city‐region solely at the receiving end of devolutionary austerity. Rather, we illustrate how the urgency of devolution was conditioned by crisis, yet concomitantly framed as a unique opportunity by the local state harnessing policy to negotiate a more fluid politics of scale. In doing so, the paper demonstrates how attempts to resolve the "local problem" of governing health and care under austerity were rearticulated as a "global opportunity" to forge new connections between place, health, and economy. Consequently, we foreground the multiple tensions and contradictions accumulating through turning to health and care to push Greater Manchester further, faster. The paper concludes by asking what the present crisis might mean for city‐regions in good health and turbulent times. Abstract : Health and care policy is increasingly promoted within competitive city‐region visions. Based on a two‐year study of health and social care devolution in Greater Manchester, England, we demonstrate how the "local problem" of governing health and care amid austerity politics was rearticulated as a "global opportunity" to forge new connections between place, health, and economy. The paper foregrounds the multiple tensions and contradictions accumulating through turning to health and care to push the city‐region further, faster.